the reflection of Quranʹs proverbs in the values of Persianʹs civilization - عبد الحسن عبد, حسام (Al-Adab Journal, 2018)
Hit Persian′s proverbs is considered an one of senior human values ​​that represent the culture and civilization of the Iranians. Not only the Persians taking them from the Quran on the hair and prose texts even inspired him to have some like them emerging, from here, the Persian proverbs inspired by the Quran has many of the senior human values.Follow researcher in his research presentation analytical approach descriptive terms divisible by three sections and as shown below:First research - the word (such as) from the perspective of linguistic terms included:1.The term goes in the encyclopedia linguistic author Dhkhaddahit proverbs of the concept according to BriqaaThe second topic - Supreme human values ​​in the Persian proverbs inspired by the Koran, containing:human value position to take advantage of hitting the Persian proverb.mentioned Persian proverbstated ideals inspired verse or Quranic text.mentioned Persian translation of the verse mentioned with her translator.Section III hit the Persian proverb emerging from the Quranic stories and contains two stories:1.objections to the bne Israelsuch as dam AlasResearcher in revenue adopted his research on a variety of sources, including:Proverbs and the wisdom of DhkhaddaDhkhaddh encyclopedia′s of language.Qur'an al magid had been translated by many known interpreter.proverbs and wisdom in works of poets.stories of proverbs. dictionary′s amed.